Pirate Adventure - Hunt Roderick; Alex Brychta (Oxford Oxford University Press, 2012)
Biff, Chip, and Kipper, along with their dog Floppy, embark on an exciting journey aboard a pirate ship after discovering a magical key. They face thrilling adventures, including outsmarting the pirates and searching for hidden treasure, before making a daring escape back home. Ideal for young readers, this story blends fantasy and adventure to engage and entertain.
Biff, Chip, Kipper, and Floppy find themselves on a pirate ship after discovering a magical key that transports them into a different world. They must outwit the pirates and find their way back home.
Keywords: Pirates